Skull shape variation in extant pangolins (Pholidota: Manidae): allometric patterns and systematic implications. Issue 1 (9th November 2019) - Ferreira-Cardoso, Sérgio; Billet, Guillaume; Gaubert, Philippe; Delsuc, Frédéric; Hautier, Lionel
Abstract: Pangolins are among the most endangered groups of mammals, comprising eight extant species delineated into three genera. Despite several studies dedicated to their skeletal anatomy, the potential taxonomic insight from cranial morphological variation in extant Pholidota is yet to be assessed with modern geometric morphometric methods. We present the first comprehensive study on the cranial morphology of extant pangolins and discuss its implications for the taxonomy and evolution of the group. We performed landmark-based morphometric analyses on 241 museum specimens to describe the variation in skull shape in seven of the eight extant species. Our analyses revealed genus- and species-level morphological discrimination, with Asian species ( Manis spp.) being grouped together, whereas African pangolins present distinct skull shapes between small ( Phataginus spp.) and large ( Smutsia spp.) species. Analyses of allometry also identified a set of traits whose allometric trajectories distinguish Asian from African specimens. Finally, we uncovered intraspecific variation in skull shape in white-bellied pangolins ( Phataginus tricuspis ) that partly corroborates recent DNA-based differentiation among biogeographically distinct populations. Overall, our results shed light on the morphological diversity of the skull of these enigmatic myrmecophagous mammals and confirm the genus-level classification and cryptic diversity within the white-bellied pangolin revealed by molecular phylogenetics.